A twice‐daily barometric pressure record from Durham Observatory in north‐east England, 1843–1960. Issue 1 (25th October 2021) - Burt, Stephen D.
Abstract: A twice‐daily record of barometric pressure exists for Durham Observatory (54.768 °N, 1.584 °W, barometer cistern 107.3 m above mean sea level, MSL ) from 23 July 1843 to 31 December 1960 and is published here for the first time. The Durham record, which is 98.7% complete, is by far the longest digital barometric pressure series in northern England and fills a very large temporal and spatial gap in the International Surface Pressure Database (ISPD: Cram et al, [2015] Geoscience Data Journal, 2, 31–46). In what is believed to be the first study of its kind, the record has been independently quality‐controlled against the NOAA–CIRES–DOE Twentieth Century Reanalysis version 3 (20CRv3; Slivinski et al., [2019] Quarterly Journal of the Royal Meteorological Society, 145, 2876; Slivinski et al., [2021] Journal of Climate, 34, 1417–1438), which did not include the Durham records in its assimilation set. This paper describes the instruments used and their exposure, the sources of the record, digitization work undertaken to generate the digital time series (including quality control assessments using 20CRv3) and reduction to mean sea level pressure from station level observations, and examines consistency over the period of record against 20CRv3, concluding with a summary of monthly and annual means and extremes over the 117 year series and the details of the new dataset. Abstract : Graphical AbstractThe contents of this page will be used as part of the graphical abstract of html only. It will not be published as part of main article.A twice‐daily record of barometric pressure exists for Durham Observatory (54.768 °N, 1.584 °W, barometer cistern 107.3 m above mean sea level, MSL) from 23 July 1843 to 31 December 1960, and is published here for the first time. The Durham record, which is 98.7% complete, is by far the longest digital barometric pressure series in northern England, and fills a very large temporal and spatial gap in the International Surface Pressure Database (ISPD). In what is believed to be the first study of its kind, the record has been independently quality‐controlled against the NOAA–CIRES–DOE Twentieth Century Reanalysis version 3 (20CRv3), which did not include the Durham records in its assimilation set.